REALISASI PENDAPATAN ASLI DAERAH DI SEKTOR PARIWISATA KABUPATENTULUNGAGUNG - Ananda Galuh Puspita; Cindy Claudia Radha Avita (Universitas Tulungagung, 2021)
AbstractThis study aims to find out how the income realization in the tourism sector in Tulungagung Regency. The diversity of tourism objects in Tulungagung has become an asset or source of local revenue. Another advantage obtained is the creation of jobs in the community and an increase in the tourism industry. This study uses a qualitative method. Where the data used is sourced from secondary data in the form of journals, articles and books. Qualitative research methods are used to examine the problem. The information collection technique used is groundwork information abstraction in the form of secondary information. In this study, the tourism sector in Tulungagung Regency was studied through the use of media. The use of the media in question is the web. Documentation of research reports, and journals from around the world. The results of this study show that regional financial income comes from local taxes and levies, one of which is in the tourism sector. The Tulungagung Regency Government has a revenue target in the tourism sector, but it has not been met due to the COVID-19 pandemic. The income of the tourism sector is very influential on the Regional Original Income (PAD) of Tulungagung Regency.AbstrakPenelitian ini bertujuan mengetahui bagaimana realisasi pendapatan pada sektor pariwisata di Kabupaten Tulungagung. Keanekaragaman objek wisata di Tulungagung telah menjadi suatu asset atau sumber dari Pendapatan Asli Daerah . Keuntungan lain yang didapatkan yaitu terciptanya lapangan kerja di masyarakat serta peningkatan industri pariwisata. studi ini memakai metode kualitatif. Dimana data yang dipakai bersumber dari data sekunder yang berupa jurnal, artikel maupun buku. Metode penelitian kualitatif digunakan untuk meneliti masalah tersebut. Teknik pengumpulan informasi yang digunakan adalah abstraksi information groundwork yaitu berupa information sekunder. Dalam penelitian ini, sektor pariwisata di Kabupaten Tulungagung dikaji melalui pemanfaatan media. Pemanfaatan media yang dimaksud yaitu web. Dokumentasi laporan penelitian, dan jurnal dari seluruh dunia.Hasil penelitian ini diketahui bahwa pendapatan keuangan daerahberasal dari pajak serta retribusi daerah, salah satunya di bidang pariwisata. Pemerintah Kabupaten Tulungagung memiliki target pendapatan di sektor pariwisata, namun belum terpenuhi akibat pandemi COVID-19. Pendapatan sektor pariwisata sangat berpengaruh terhadap Pendapatan Asli Daerah (PAD) Kabupaten Tulungagung.